Alternative of high voltage multipliers utilizing CockcroftWalton multiplier blocks for 220 V and 50 Hz input - Anurak Jaiwanglok; Kei Eguchi; Amphawan Julsereewong; Pittaya Pannil (My University, 2020)
In order to be practical for converting 220 V and 50 Hz AC input into high DC output ranged between 3.5 and 4.0 kV to create underwater shockwaves in non-thermal technique for processing foods, this article presents an alternative approach for modifying conventional high voltage multipliers without magnetic elements, which are based on the use of parallel-connected Cockcroft–Walton multiplier blocks (CWMBs) in bipolar structure. The basic three-stage CWMB scheme as well as the effect of different capacitor values on its output is described. The modified high voltage multiplier with improved response speed consists of a full-wave rectifier (FWR), a two-phase driver block, a parallel-connected positive CWMB, and a parallel-connected negative CWMB. Both output voltage and power efficiency of the proposed scheme can be demonstrated by theoretical analysis results. Moreover, simulation results showing the characteristics of the proposed high voltage multiplier are also included.
Keywords: Voltage multiplier; Rectifier (neural networks); High Voltage; Advanced DC-DC Converters